TRANSFORMASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS DELAPAN DIMENSI PROFIL LULUSAN PEMBELAJARAN MENDALAM (DEEP LEARNING) UNTUK MENJAWAB TANTANGAN ABAD 21 - Saridudin; Saridudin, Saridudin (HASBUNA : Jurnal Pendidikan Islam, 2025)
This article discusses the transformation of Islamic Religious Education learning based on eight dimensions of graduate profiles within the framework of in depth learning as an effort to answer the challenges of the 21st century. The various challenges of globalization, modernization, digitalization, moral degradation, and spiritual crisis require education to produce graduates who are not only cognitively intelligent, but also emotionally, spiritually, morally, and socially mature, and master 21st century skills. The eight dimensions of the in depth learning graduate profilefaith and piety towards God Almighty, citizenship, critical reasoning, creativity, collaboration, independence, health, and communication are integrated into Islamic Religious Education learning through innovative approaches such as project based learning, problem based learning, technology integration, and collaborative learning. This article emphasizes that teachers have various roles in education, such as curriculum designers, collaborating between schools, families, and communities, and evaluating learning based on competencies and character, which are the primary keys to successful learning. Thus, the transformation of Islamic Religious Education towards participatory reflective and competency oriented learning is expected to produce a faithful generation, has noble morals, is competitive, and is able to face the complexity of problems in the global era